Cognitive-behavioural interventions for children who have been sexually abused. - Macdonald, G; Higgins, J; Ramchandani, P (2006)
BACKGROUND: Despite differences in perceptions of what constitutes child sexual abuse there is a general consensus amongst clinicians and researchers that this is a substantial social problem which affects large numbers of children and young people worldwide. The effects of sexual abuse manifest themselves in a wide range of symptoms, including fear, anxiety, post-traumatic stress disorder and behaviour problems such as externalising or internalising, or inappropriate sexual behaviours. Child sexual abuse is associated with increased risk of psychological problems in adulthood. Knowing what is most likely to benefit children already traumatised by these events is important. OBJECTIVES: The aim of this review was to assess the efficacy of cognitive-behavioural approaches (CBT) in addressing the immediate and longer-term sequelae on children who have been sexually abused. SEARCH STRATEGY: The Cochrane Central Register of Controlled Trials (CENTRAL) (Issue 5, 2005), MEDLINE (1966-November 2005); EMBASE (1980-November 2005); CINAHL (1982-November 2005), PsycINFO (1897-November 2005); LILACS (1982-November 2005); SIGLE (1980 to November 2005) and the register of the Cochrane Developmental, Psychosocial and Learning Problems Group (November 2005) were searched. SELECTION CRITERIA: Included studies were randomised or quasi-randomised controlled trials investigating the efficacy of cognitive behavioural therapy on children and adolescents up to age 18 years who had experienced sexual abuse. DATA COLLECTION AND ANALYSIS: Titles and abstracts identified in the search were independently assessed for eligibility by two reviewers (GM and PR). Data were extracted and entered into REVMAN (JH and GM), and synthesised and presented in both written and graphical form (forest plots). MAIN RESULTS: Ten trials, including 847 participants, were included in this review. Data suggest that CBT may have a positive impact on the sequelae of child sexual abuse, but most results were statistically non-significant. AUTHORS' CONCLUSIONS: The review confirms CBT's potential as a means of addressing the adverse consequences of child sexual abuse, but highlights the tenuousness of the evidence base and the need for more carefully conducted and better reported trials.